Characteristics of cadmium ion sorption from aqueous solutions on copper(II) sulfide at different temperatures and pH - Bulgakova, A.V.; Sofronov, D.S.; Bryleva, E.Yu.; Chebanov, V.A. (Functional Materials, 2016)
Characteristics of cadmium ion sorption from aqueous solutions on copper(II) sulfide at different temperatures and pH were investigated. The sorption process obeys to the Langmuir equation, which is used to calculate the sorption capacities of copper(II) sulfide. It is shown that the sorption capacity increases with increase of pH and decrease of temperature. The sorption capacity changes from 5.6 mg/g at pH 5 and 308 K to 15.2 mg/g at pH 7 and 288 K. Optimization of the conditions permits to improve the copper(II) sulfide sorption capacity. The pH changes during the sorption obey to the Kurbatov equation with the sorption process being the ion exchange reaction.